Atividade antiproliferativa de derivados sulfonilados de goniotalamina e piplartina em células MCF-7: indução de estresse oxidativo e danos ao DNA - Nacif, Julia Louise Moreira (2024)
Cancer is the second leading cause of death in the world and breast cancer is the most common among women. Breast cancer is a complex and heterogeneous disease comprising different tumor subtypes. The introduction of new therapeutic approaches has contributed to increase the quality of life and the survival rate of patients, but resistance to the available drugs is very frequent, therefore it is important to expand the available therapeutic arsenal for breast cancer. In this context, natural products have been widely explored, as many antineoplastic drugs are of natural origin or were obtained from natural prototypes. Therefore, the present study aims to explore the antitumor potential of sulfonyl derivatives of goniothalamin (compound 3) and piplartine (compound 6) on MCF-7 breast cancer cell line. The mechanism of action of these compounds on tumor cells was investigated through assays evaluating cell viability, clonogenic capacity, cell cycle progression, senescence, apoptosis, oxidative stress and gene expression of proteins related to these processes. The results obtained showed that compounds 3 and 6 are more cytotoxic against the MCF-7 cell line compared to the non-tumor cell line CCD-1059Sk (skin-derived fibroblasts). The compounds also completely inhibited colony formation on MCF-7 cell line. The antiproliferative activity of the studied compounds was partially prevented in the presence of the antioxidant N-acetylcysteine. Compound 3 altered the dynamics of cell cycle progression, inducing accumulation of cells in the G0/G1 and G2/M phases, depending on the concentration used. Compound 6 at 3.5µM promoted an increase in the G2/M population and a decrease in the frequency of cells in the S phase compared to the control groups. At 7.0 µM, compound 6 was cytotoxic against MCF-7, as demonstrated by an increase in the sub-G1 population and an increase in the frequency of apoptotic cells. The antiproliferative and proapoptotic activities were associated with the ability of the studied compounds to modulate the gene expression profile of cell cycle and apoptosis regulators (CDKN1A, MYC, CCNB1, CCND1, BAX and BCL2) in response to oxidative stress and DNA damage. Compound 3 induced cellular senescence, while compound 6 modulated the PI3K/AKT and MAPK/ERK signaling pathways and induced apoptosis. Therefore, these compounds represent interesting prototypes for the development of drugs against breast cancer.